Viral Infections in Immunocompromised Hosts (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue comprises 11 manuscripts and 1 editorial. The manuscripts include 4 research papers and 7 reviews, with one correction to a review article. All contributions focus on viral infections in immunocompromised hosts.